2014
DOI: 10.1620/tjem.232.301
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Otitis Media Caused by Mucoid<i> Streptococcus Pyogenes</i> in a Previously Healthy Adult

Abstract: JapanStreptococcus (S.) pyogenes is well recognized as the most common pathogen causing pharyngotonsillitis in school-age children. In Japan, mucoid Streptococcus pneumoniae is well known as a causative agent of severe acute otitis media (AOM); however, mucoid S. pyogenes has rarely been reported. To the best of our knowledge, this is the first report of an AOM patient caused by mucoid S. pyogenes in Japan. A 36-year-old previously healthy female was referred to our hospital with suspicion of cerebrospinal oto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Determination of species identification: DNA was extracted from the β-hemolytic streptococcal isolates by suspending in TE buffer and boiling at 97°C for 10 min as previously described (14). We identified the βhemolytic streptococcal strains at the species-level based on 16S rRNA sequencing data (13,15) (Table 1). The isolates identified were unambiguously identified, with ≥ 98.7% similarity to the 16S rRNA sequence of the corresponding strain.…”
Section: Collection Of Bacterial Isolates and Background Of Companionmentioning
confidence: 99%
“…Determination of species identification: DNA was extracted from the β-hemolytic streptococcal isolates by suspending in TE buffer and boiling at 97°C for 10 min as previously described (14). We identified the βhemolytic streptococcal strains at the species-level based on 16S rRNA sequencing data (13,15) (Table 1). The isolates identified were unambiguously identified, with ≥ 98.7% similarity to the 16S rRNA sequence of the corresponding strain.…”
Section: Collection Of Bacterial Isolates and Background Of Companionmentioning
confidence: 99%
“…This very low macrolide resistance rate was further confirmed by a recent study conducted in the same area (Olivieri et al, 2015 ). In a study conducted in Portugal between 2,000 and 2,005, the genotype emm75/ST150 was significantly associated with pharyngitis (Friaes et al, 2012 ); however, interestingly, a mucoid form of a GAS strain M75/ST49 has recently been reported to cause a severe acute otitis media (Kakuta et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The capsule polysaccharide is the major virulence determinant of S. pneumoniae [ 11 ], particularly in hosts lacking type-specific antibodies of sufficient quantity or avidity [ 12 ]. Moreover, previous studies demonstrated that the mucoid phenotype, which is characterized by the presence of hyaluronic acid capsular polysaccharide in Streptococcus pyogenes , is a key virulence determinant associated with severe S. pyogenes infections [ 13 , 14 ]. The mucoid phenotype of S. pneumoniae may also show higher pathogenicity than the non-mucoid phenotype; therefore, it is important to characterize S. pneumoniae , especially the mucoid phenotype, with regard to antibiotic susceptibility.…”
Section: Discussionmentioning
confidence: 99%